EMC and functional safety of automotive electronics - Borgeest, Kai‏ ‎ 1967- (Institution of Engineering and Technology, 2018)
Electromagnetic compatibility (EMC) deals with the unintentional propagation and reception of electromagnetic energy which may cause disturbances or even physical damage in electronic or electromechanical systems. With the increase in number and density of electronic devices and systems in modern vehicles, EMC has become a substantial concern and a key cause of malfunction of automotive electronics. This book explores electromagnetic compatibility in the context of automotive electronics, with a close relation to functional safety as required by ISO 26262. Topics covered include an introduction to automotive electronics; electrical drives and charging infrastructure; fundamentals of functional safety; fundamentals of EMC, signal and power integrity; the legal framework; EMC design at the ECU Level; EMC design at the system level and in special subsystems; modelling and simulation; and test and measurement for EMC.
Keywords: Automobiles -- Electronic equipment.; Electromagnetic compatibility.; elektronické knihy; electronic books